Santa Claus is comin' to town - Kellogg, Steven; Coots, J. Fred 1897-1985.; Gillespie, Haven 1888-1975.; Steven Kellogg ([New York] : HarperCollins, 2004)
A small bear visits Santa's workshop and finds wonderful, shining red and green toys and shares news from Santa with Maddy and Peter.
2 leaves fold out to form an oversized pre-flight scene of Santa and his sleigh.
96867
Keywords: Children's songs -- United States; Toy and movable books; Santa Claus; Christmas music; Songs; Christmas stories